Identification of Candida albicans in the Urine of Pregnant and Non-Pregnant Women with UTI at X Hospital, Jember - Melia Pratiwi; Hartalina Mufidah; Ahdiah Imroatul Muflihah; Rian Anggia Destiawan (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2025)
Background: Urinary tract infections (UTIs) are a common condition in older women, but adolescents can also experience them. This condition can lead to other conditions, such as cancer and urinary tract stones. Candida albicans infection is one cause of UTIs, which is highly prevalent in both pregnant and non-pregnant women. This is due, in part, to hormonal influences. Purpose: This study aimed to knowing the difference in the growth of Candida albicans fungus in the urine of pregnant and non-pregnant women suffering from urinary tract infections. Methods: The study design was cross-sectional with 30 urine samples from pregnant women and 30 urine samples from non-pregnant women with urinary tract infections. The study was conducted from March to May 2025. The sampling technique used was purposive sampling. The data obtained were processed using SPSS chi-square test. If the chi-square test requirements were not met, decision-making was based on the fisher's exact test value. Results: Positive results for Candida albicans in the urine of UTI in pregnant women were 13 samples and 3 negative samples, while in non-pregnant women, 9 positive samples and 1 negative sample were obtained. UTI did not have a significant effect on the growth of Candida albicans because the statistical analysis of the chi-square test obtained a p-value of 0.370, where the p-value is greater than 0.05. Conclusions: There was no difference in the growth of Candida albicans fungus in the urine of pregnant and non-pregnant women with UTI.